Preliminary Analysis on Organizational Factors Influencing Effective Construction Risk Management: A case study of Nigerian Construction Companies (Sains Humanika, 2016)
An increased demand has been placed on construction projects for more accountability to their clients with measure to the company products and services. However, this demand is because of innumerable antecedent factors repelling effective risk management in construction projects. Therefore, finishing the projects is not only the concern of the industries but also managing the risks involved with the projects. The impacts of effective risk management on the performance of these industries are as well important. The objective of this study is twofold: (i) to propose an inclusive framework which comprises of the antecedent factors proposed in the framework to improve effective risk management in Nigeria construction companies (ii) to measure the instrument used for the preliminary analysis in this study. Data were collected from forty respondents using seventy-five items instrument. SPSS software was used to analyze the data collected for the pilot test. The results of the Cronbach’s Alpha test disclosed a strong internal reliability of the overall instrument and the construct. This research is significant because it explores the implementation of some organizational factors which will influence construction risks and will also improve effective risk management in Nigeria construction projects, and the validation of the instrument which requires further exploration of the constructs in future study
Keywords: Effective construction risk management; framework; instrument; validation and reliability